2021
DOI: 10.3390/ijms22094749
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Intake Impairs the Synergistic Vasomotor Manifestation of Nitric Oxide and Hydrogen Sulfide in Rat Aorta

Abstract: In this study, we evaluated the effect of eight weeks of administration of 10% fructose solution to adult Wistar Kyoto (WKY) rats on systolic blood pressure (SBP), plasma and biometric parameters, vasoactive properties of the thoracic aorta (TA), NO synthase (NOS) activity, and the expression of enzymes producing NO and H2S. Eight weeks of fructose administration did not affect SBP, glycaemia, or the plasma levels of total cholesterol or low-density and high-density lipoprotein; however, it significantly incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
4
0
Order By: Relevance
“…Nevertheless, we confirmed that, unlike in control rats, H 2 S significantly participated in maintaining endothelial function in the MLN-4760 group (unlike in the control group). Similar compensatory crosstalk between NO and H 2 S signaling has already been declared in fructose-fed normotensive rats [ 62 ] as well as in SHRs, where the increased participation of H 2 S in vasorelaxation after acute NO inhibition could be considered a salvage mechanism in cases of endogenous NO deficiency [ 10 ]. Similarly, we confirmed a stronger anticontractile action of H 2 S produced by perivascular adipose tissue surrounding the thoracic aorta in hypertriglyceridemic rats [ 63 ], suggesting that H 2 S signaling can be stimulated as a balancing pathway in different pathological conditions.…”
Section: Discussionsupporting
confidence: 56%
“…Nevertheless, we confirmed that, unlike in control rats, H 2 S significantly participated in maintaining endothelial function in the MLN-4760 group (unlike in the control group). Similar compensatory crosstalk between NO and H 2 S signaling has already been declared in fructose-fed normotensive rats [ 62 ] as well as in SHRs, where the increased participation of H 2 S in vasorelaxation after acute NO inhibition could be considered a salvage mechanism in cases of endogenous NO deficiency [ 10 ]. Similarly, we confirmed a stronger anticontractile action of H 2 S produced by perivascular adipose tissue surrounding the thoracic aorta in hypertriglyceridemic rats [ 63 ], suggesting that H 2 S signaling can be stimulated as a balancing pathway in different pathological conditions.…”
Section: Discussionsupporting
confidence: 56%
“…Incubation with the H 2 S scavenger reduced endothelium-dependent relaxation in all experimental groups, except for the control SHR, and ZOFE treatment had no effect on these vasoactive responses, suggesting that H 2 S participated in maintaining endothelial function in MLN-treated rats, which could be considered a compensatory mechanism. This observation corresponds with other findings that declare that H 2 S signaling can be stimulated in different pathological conditions, e.g., in fructose-fed normotensive rats [ 58 ] as well as in SHRs, where the increased participation of H 2 S in vasorelaxation could counterbalance endogenous NO deficiency [ 53 ]. The decreased expression of H 2 S-producing enzymes in the MLN-treated rats could be explained by negative feedback regulation to maintain a constant H 2 S level.…”
Section: Discussionsupporting
confidence: 91%
“…Arterial endothelial dysfunction was described in studies using different fructose-fed protocols, and it was related to increased oxidative stress, reduced production or availability of nitric oxide, and increased levels of uric acid and endothelin-1 [ 41 , 42 , 43 ]. The presented results as well as the observations of other authors demonstrate that the substances released from PVAT could participate in these pathological processes [ 17 , 44 ].…”
Section: Discussionmentioning
confidence: 99%